Inter-rater Reliability of the Partner Behavior Support Profile. - Kipp, Dana; Riske, Tania; Myers, Rebecca (My University, 2009)
Effective and successful transitioning of persons with traumatic brain injury (TBI) back into their everyday lives and communities is linked to the presence of supports within that individual's community settings, including close partners such as spouses, siblings, parents, and friends. This study examines effective partner training with transparent explanations and rationales to foster sustainable, generalized treatment outcomes that will provide the necessary long-term suppor for the person with TBI.
Color poster with text, tables, and charts.
Keywords: Brain damage--Patients--Family relationships; Brain damage--Patients--Rehabilitation; Brain damage--Patients--Social networks; Caregivers--Family relationships; Caregivers--Training of; Posters